Unconscious information processing of table tennis athletes in a masked priming paradigm: an event-related potentials (ERP) study - Fanying Meng; Lijiao Chen; Chun Xie; Jiadong Zheng; Ning Chen; Fanghui Qiu; Jiaxian Geng (PeerJ)
Background Unconscious information processing is enhanced among athletes for sports-specific contexts. Whether this enhancement is transferable to general contexts is unknown. This study explored unconscious information processing and brain activity in highly trained table tennis athletes and non-athletes in general contexts. Methods Twenty table tennis athletes (six females, mean age = 20.38 ± 1.28, mean ± standard error) and 21 aged-matched college students (eight females, mean age = 19.81 ± 1.29) were recruited for this study. Each participant first performed a masked priming task. In this task, a prime stimulus (arrows pointing left or right) was presented, followed by a visual mask (arrows pointing in both directions) and then a target stimulus, the target stimulus consisted of arrows pointing in the same direction as the prime for congruent stimuli or in the opposite direction for incongruent trials, while the P3 component of the event-related potential was simultaneously recorded in the brain. As a control, participants then performed a prime identification task (the subjective threshold test and the objective threshold test) to determine whether they could consciously detect the priming arrows. Reaction times, error rates, P3 latency and P3 peak amplitude were analyzed to examine the unconscious information processing of table tennis athletes in general contexts. Results Participants responded with the direction of the target arrow and were not consciously aware of the priming stimulus. Athletes responded faster in comparison of non-athletes. Athletes and non-athletes responded faster and committed fewer errors in incongruent vs. congruent conditions. In addition, the years of table tennis training were negatively correlated with the magnitude of negative compatibility effect. Both groups displayed longer P3 latencies, a measure of inhibitory control, in the incongruent vs. congruent trials. However, athletes displayed higher P3 peak amplitudes, reflecting larger attention resource input, and longer P3 latencies than non-athletes in central brain sites. Conclusion Unconscious information processing among table tennis athletes is not prominent in general contexts, but may be limited to the sports-specific context or more complex cognitive tasks.